Hubungan Antara Karbohidrat dan Lemak dengan Kejadian Overweight pada Remaja di SMA Muhammadiyah 4 Kartasura Kabupaten Sukoharjo: Asupan Karbohidrat: Asupan Lemak: Overweight: Remaja - Diyan Tri Wulandari (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2017)
ABSTRACT: Overweight in adolescents can be caused by excessive food or not in accordance with the number of their needs and if it’s left can cause various diseases such as diabetes mellitus, hypertension, and even coronary heart. Humans tended to like foods that contain fat and sugar. High energy foods such as carbohydrates and fats can increase the prevalence of more nutrients. This study aims to determine the relationship between carbohydrate intake and fat with the incidence of overweight in adolescents in SMA Muhammadiyah 4 Kartasura Sukoharjo District. This research used crosssectional study design with research subjects of X - XII class students which fulfilled criteria as many as 40 respondents selected using systematic random sampling method. The data of fat and carbohydrate intake was calculated from the average intake with the method of estimation of food record 24 hours for 3 days using Nutrisurvey. Measurement of nutritional status in respondents using IMT/U. The results of this study indicate as many as 40% of respondents have more nutritional status and 30% of respondents have more fat intake. Pearson Product Moment test results showed that carbohydrate intake with overweight occurrence showed p = 0.230 which means no relationship, whereas for fat intake with overweight occurrence showed p value = 0.025 which means there is correlation between fat intake with overweight occurrence, value R = 0.355, RR = 3.37, 95% CI = 1,224 - 9,279 which means respondents with excess fat intake have an overweight risk. This study recommends that students be able to control and reduce the types of foods that are especially high in fat and carbohydrates to minimize the incidence of more nutrients.